Solitary paralysis of the flexor pollicis longus muscle after minimally invasive elbow procedures: Anatomical and clinical study of the anterior interosseous nerve - Dolderer, Juergen H.; Prandl, Eva Christina; Kehrer, Andreas; Beham, Alfred; Schaller, Hans Eberhard; Briggs, Christopher; Kelly, Jack L. (Plastic and Reconstructive Surgery, 2011)
Background: The origin of the flexor pollicis longus muscle can vary, causing compression of the anterior interosseous nerve in the forearm. The topographic relationship of the flexor pollicis longus to the median and anterior interosseous nerves must be considered when these nerves are decompressed. The anterior interosseous nerve is a motor nerve supplying the flexor pollicis longus, the flexor digitorum profundus, and the pronator quadratus. Unusual etiologic conditions can occasionally cause isolated neuropathy of the flexor pollicis longus branch from the anterior interosseous nerve. Methods: Six patients presented with isolated paralysis of the flexor pollicis longus, four following venipuncture in the cubital fossa and two following arthroscopy of the elbow joint. Cadaveric dissections were performed to examine any anatomy clinically relevant to the above techniques. The structure of the flexor pollicis longus nerve branch at different levels was examined with macroscopic and microscopic dissections and immunohistochemistry. Results: In each case, clinical symptoms resolved completely with conservative treatment. Dissection of cadaver arms showed that the nerve branch to the flexor pollicis longus joins the anterior interosseous nerve in the proximal third of the forearm and shares a common epineurium, but has its own fascicle up to the proximal aspect of the elbow. The branch to the flexor pollicis longus has no proximal interneural cross-connections up to the main trunk of the median nerve. Conclusion: The variable relationship of the superficial cubital veins to the underlying muscles and minimally invasive approaches to the elbow joint may cause an isolated neuropathy in the motor branch to the flexor pollicis longus, with a resultant solitary paralysis of the muscle. Copyright © 2011 by the American Society of Plastic Surgeons.
CRIS-Team Scopus Importer:2024-12-11